Evaluation of Serum Inflammatory Biomarkers such as C-Reactive Protein, Interleukin-6, and Tumor Necrosis Factor-Alpha in patients with Chronic Rhinosinusitis: A Clinical Study - Anam Arshad, Iram Arshad, Hameedullah Achakzai, Qurratulain, Nasar Iqbal Ranjha, Rafaqat Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic rhinosinusitis (CRS) is a persistent inflammatory disorder of the nasal and paranasal sinuses, associated with significant morbidity and impaired quality of life. Increasing evidence suggests that systemic inflammation plays a crucial role in its pathophysiology. This study aimed to evaluate serum inflammatory biomarkers, including C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α), in patients with CRS and to assess their association with disease severity. Methods: This cross-sectional clinical study was conducted from June 2022 to June 2023 at Central Park Medical College, Lahore, and Bolan Medical College, Quetta, Pakistan. A total of 100 participants were enrolled, including 60 patients with clinically and radiologically confirmed CRS and 40 healthy controls. Serum levels of CRP, IL-6, and TNF-α were measured using enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using SPSS version 26, with p ≤ 0.05 considered statistically significant. Results: Serum levels of CRP, IL-6, and TNF-α were significantly higher in CRS patients compared to controls (p < 0.001). Mean CRP levels were 9.1 ± 2.7 mg/L in patients versus 2.3 ± 1.0 mg/L in controls. IL-6 and TNF-α levels also showed marked elevation. Furthermore, biomarker levels increased progressively with disease severity, demonstrating a strong positive correlation with clinical severity scores. Conclusion: Elevated serum inflammatory biomarkers in CRS patients indicate a significant systemic inflammatory component. These biomarkers may serve as useful tools for disease severity assessment and monitoring therapeutic response, with potential implications for improving clinical management strategies. Keywords: Chronic rhinosinusitis, C-reactive protein, Interleukin-6, Tumor necrosis factor-alpha, Inflammation, Biomarkers.